2018
DOI: 10.1007/s12010-018-2852-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lactic Acid Production by Adaptive Evolution of Lactobacillus paracasei on Agro-industrial Substrate

Abstract: The aim of this study was to perform the adaptation of Lactobacillus paracasei NRRL B-4564 to substrate through adaptive evolution in order to ensure intensive substrate utilization and enhanced L (+)-lactic acid (LA) production on molasses-enriched potato stillage. To evaluate the strain response to environmental conditions exposed during the adaptation process and to select the best adapted cells, the antioxidant activity and LA-producing capability were assessed in batch fermentation. The most promising ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…The DPPH scavenging activity of L. paracasei was higher than that of L. casei (27.5%) and L. delbrueckii (24.0%) at the same cell concentration of 10 9 CFU mL −1 . We have previously shown that the antioxidant capacity of L. paracasei NRRL B‐4564 was highly dependent on environmental conditions, and a significant increase in antioxidant activity could be provoked by strain exposure to certain pro‐oxidative compounds . These findings indicate that L. paracasei may exert an important role in protection from oxidative stress, providing the benefit to the gut microbiota of host.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The DPPH scavenging activity of L. paracasei was higher than that of L. casei (27.5%) and L. delbrueckii (24.0%) at the same cell concentration of 10 9 CFU mL −1 . We have previously shown that the antioxidant capacity of L. paracasei NRRL B‐4564 was highly dependent on environmental conditions, and a significant increase in antioxidant activity could be provoked by strain exposure to certain pro‐oxidative compounds . These findings indicate that L. paracasei may exert an important role in protection from oxidative stress, providing the benefit to the gut microbiota of host.…”
Section: Resultsmentioning
confidence: 96%
“…Cell disruption was performed by ultrasonic homogenizer (Sonopuls HD 2200, BANDELIN electronic, Berlin, Germany) for five 1 min intervals (1 min on/1 min off, 35% amplitude), ensuring a constant cooling. Cell debris was removed by centrifugation (8000 × g , 10 min, 4 °C) and the resulting supernatant (intracellular extract), along with intact cells, was subjected to 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging assay as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Some studies have attempted to evolve yeast strains for lactate production to leverage its property to tolerate lower pH [22]. There are also reports on L-LA production from lignocellulosic substrate by SSF using different strains evolved for improved antioxidant property [23] and e cient xylose assimilation [24]. Although enzyme loading is a critical techno-economic factor, there are not many detailed reports available on optimization or minimization of enzyme loading to achieve higher product to enzyme ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have attempted to evolve yeast strains for lactate production to leverage its property to tolerate lower pH [26]. There are also reports on L-LA production from lignocellulosic substrate by SSF using different strains evolved for improved antioxidant property [27] and e cient xylose assimilation [28]. Although enzyme loading is a critical techno-economic factor, there are not many detailed reports available on optimization or minimization of enzyme loading to achieve higher product to enzyme ratio (PER).…”
Section: Introductionmentioning
confidence: 99%